Tests of transitivity in choices between fixed and variable reinforcer delays. - Mazur, J E (1987)
This experiment tested for transitivity in pigeons' choices between variable-time (VT) and fixed-time (FT) schedules. In a discrete-trials procedure, a subject chose between two alternatives by making a single key peck. Each choice was between a "standard alternative," which was the same schedule throughout a condition, and an "adjusting alternative," in which the delay to reinforcement was systematically increased or decreased many times a session. These adjustments enabled an approximate indifference point to be identified--the value of the adjusting delay at which the subject chose each alternative about equally often. Each test of transitivity involved four conditions. In one, the standard alternative was a variable-time schedule with a 2-s reinforcer, and the adjusting alternative also delivered a 2-s reinforcer. A second condition was similar except that the adjusting alternative delivered a 5-s reinforcer. The indifference point from each of these conditions was then converted to a fixed-time schedule for subsequent comparisons in the third and fourth conditions, respectively. Each of these last two conditions compared one of the fixed-time schedules (based upon the previous conditions and including their different reinforcer durations) with an adjusting schedule that delivered the alternative reinforcer duration, to determine whether the obtained indifference points would be those predicted from the prior alternative-duration comparisons with the VT schedule. There was little evidence for intransitivity of choice: Averaged across subjects and replications, the obtained indifference points deviated from perfect transitivity by less than 8%, and these deviations were not statistically significant. These results contrast with those of Navarick and Fantino (1972), who found frequent violations of transitivity between periodic and aperiodic schedules using a concurrent-chains procedure with variable-interval schedules in the initial links.